By-pass Marker for detecting Esophageal Varices in Patients with Chronic Liver Disease (TAJ: Journal of Teachers Association, 2018)
This study was designed to make a relation between gall bladder wall thickening (GBWT) measured by ultrasonography and esophageal varices (EV) measured byupper gastrointestinal endoscopy in chronic liver disease patients. Itwas cross- sectional descriptive study. 50 cases ofChronic Liver Disease were recruited. GBWT was measured by ultrasonography and upper gastrointestinal endoscopy was done for assessment of the presence and grade of EV in all cases. Among 50 cases, 34 (68%) were male and 16(32%) were female. Mean age (±SD) of the study population was 46.7 (±13.28) years of age. Esophageal varices were found in 42(84%) cases and 8(16%) cases had no varix. Among 42 cases of esophageal varices 9 cases had grade-I, 17 cases had grade-II and 16 cases had Grade-III esophageal varices. Gall bladder wall thickness up to 3mm was considered as normal. In this study GBWT value between (1-3) mm8 cases had no EV GBWT value between (3.1-5.9) mm ,10 cases had EV(9 cases had grade 1 and 1 case had grade 11 EV); GBWT value between (6-8.9) mm, 16 cases had grade 11 EV and GBWT value between (9-12) mm 16 cases had grade 111 EV. A significant statistical correlation was found between the level of GBWT and EV (P